2000
DOI: 10.1038/77819
|View full text |Cite|
|
Sign up to set email alerts
|

SCL and LMO1 alter thymocyte differentiation: inhibition of E2A-HEB function and pre-Tα chain expression

Abstract: Cooperation between the stem cell leukemia (SCL) transcription factor and its nuclear partners LMO1 or LMO2 induces aggressive T cell acute lymphoblastic leukemia when inappropriately expressed in T cells. This study examined the cellular and molecular targets of the SCL-LMO complex at the preleukemic stage. We show that SCL and its partners are coexpressed in the most primitive thymocytes. Maturation to the pre-T cell stage is associated with a down-regulation of SCL and LMO1 and LMO2, and a concomitant up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
258
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(273 citation statements)
references
References 46 publications
13
258
1
Order By: Relevance
“…We and others have shown that Tal1 expression perturbs thymocyte development by interfering with the expression of E47/HEB target genes (Herblot et al, 2000;O'Neil et al, 2004). Although Tal1 has been implicated in the proliferation of hematopoietic precursors (Green et al, 1991;Condorelli et al, 1997;Valtieri et al, 1998), this study suggests that Tal1 also stimulates cell cycle entry in preleukemic thymocytes.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We and others have shown that Tal1 expression perturbs thymocyte development by interfering with the expression of E47/HEB target genes (Herblot et al, 2000;O'Neil et al, 2004). Although Tal1 has been implicated in the proliferation of hematopoietic precursors (Green et al, 1991;Condorelli et al, 1997;Valtieri et al, 1998), this study suggests that Tal1 also stimulates cell cycle entry in preleukemic thymocytes.…”
Section: Discussionmentioning
confidence: 52%
“…We and others have shown that misexpression of Tal1 in the thymus alters thymocyte development by interfering with the expression of E47/HEB target genes including Rag1/2, Pre-Ta, CD4, CD5, CD3 and the TCRabchains (Herblot et al, 2000;O'Neil et al, 2001O'Neil et al, , 2004. Although Tal1 induces leukemia in mice, it does so after a long latency revealing that additional genetic events are required (Condorelli et al, 1996;Kelliher et al, 1996).…”
Section: Introductionmentioning
confidence: 93%
“…Tal1 is a protein binding partner of Lmo2 (Larson et al, 1996;Valge-Archer et al, 1994;Wadman et al, 1994Wadman et al, , 1997 suggesting that protein ± protein interaction plays a key role in T-ALL (Rabbitts, 1998). Similar e ects of Lmo1 and Tal1 transgenes on T cell development have been described (Chervinsky et al, 1999;Herblot et al, 2000).…”
mentioning
confidence: 75%
“…The LIM domain does not directly interact with DNA, but acts as an adaptor molecule for transcription factors facilitating assembly of large transcriptional complexes (Breen et al, 1998;Jurata et al, 1998;Sugihara et al, 1998). LMO1 and LMO2 have been shown to specify neuronal and haematopoietic cell lineages in combination with their transcription partners (Hinks et al, 1997;Yamada et al, 1998;Herblot et al, 2000). Misexpression of these genes by chromosomal translocation abrogates proper differentiation of cells and is oncogenic within T cells (Boehm et al, 1991;Royer-Pokora et al, 1991).…”
mentioning
confidence: 99%